Teaching Practices and Student Learning in the Introductory Research Methods Class - Diab, Rula L. (2006)
The aim of this paper was to investigate graduate students' experiences in a research methods course in an international context. The study first aimed at describing how graduate students in language at the American University of Beirut (AUB) are introduced to research by providing a detailed description of the course and secondly at exploring how these students react to and reflect on their experience in the research methods course. Semi-structured interviews with the seven students who were enrolled in the course in 2005 were conducted in February 2006. The results of the data analysis revealed five major categories: (a) aspects of the course the students found beneficial; (b) aspects of the course the students would like to change; (c) how the course changed students' views of research; (d) how the course changed students' research practices; and (e) views of first- vs. second-year graduate students. Based on the findings, several conclusions as well as specific pedagogical recommendations were made